Gametogenesis From the Early History Life Stages of the Kumamoto Oyster Crassostrea sikamea and Their Breeding Potential Evaluation - Zhang, Yuehuan; Qin, Yanping; Ma, Lai; Zhou, Zihua; Xiao, Shu; Ma, Haitao; Pan, Ying; Li, Jun; Yu, Ziniu (Frontiers in Physiology, 2019)
The Kumamoto oyster, Crassostrea sikamea, is native to Southeast Asia, including China, Japan and Korea, and is an important traditional wild fishery resource. Although this oyster’s early gametogenesis was reported in Mexico, no relative research was found on the breeding potential using early forming gametes. We re-examined the gametogenesis of C. sikamea during early life history in southern China and further divided it into three phases: sex differentiation (1 month old, shell height 2-3 mm), physiological maturity (2 months old, shell height 3-5 mm) and functional maturity (3 months old, shell height 9-12 mm). The breeding potential was evaluated using four sets of gametes from parent oysters of different ages (2, 3, 6 and 15 months old). The physiologically mature gametes were not suitable for artificial hatchery due to the low production of eggs, and yielding a high deformity rate of D larvae (95.47±1.25%) and heavy larval morality (90.23±1.84%) post-fertilization. However, progeny from functionally mature gametes grew significantly faster than those of other age groups, with no significant differences in fertilization, hatching level or survival of progeny among them. This study clearly demonstrates that the first batch of functionally mature gametes can develop normally and produce viable progeny, suggesting that artificial hatchery of C. sikamea is completely feasible using parent oysters from 3 months old and onwards. Furthermore, this hatchery method can effectively shorten the breeding cycle and accelerate the breeding process.